Effective fingerprinting database construction through digital map-based RF signal modeling and partial measurements in indoor environments - Jung Ho Lee; Taehun Kim; Youngsu Cho; Juil Jeon; Kyeongsoo Han; Taikjin Lee (ETRI Journal)
This paper presents a radio-frequency (RF) signal modeling technology thatbuilds a fingerprinting database for indoor localization quickly and accurately.Fingerprinting-based localization technology uses location-specific signal char-acteristics as a database; therefore, it is less sensitive to multipath problems.The proposed approach predicts signal propagation paths and calculates atten-uation based on an indoor map, reducing infrastructure installation and datacollection time. Because the indoor map lacks accurate information about allstructures, the modeling results contain errors when compared to measure-ments. To address this, measurements from a partial area improve modelingaccuracy by accounting for received signal strength changes caused by indoorstructures. In experiments with seven beacons, the proposed database con-struction method achieves an average error of 5.16 dBm and a localizationerror of 1.61 m, comparable to the 1.14-m error in measurement-based data-bases, while reducing database construction time by 41.06%. These resultsdemonstrate the effectiveness of the proposed technology in rapidly and accu-rately building databases for indoor localization.